Introducing exaptation theory to social enterprise innovation: case study on the Circular Economy Innovation Communities (CEIC) project - Liu, Zheng; James, Steffan; Samuel, Anthony; White, Gareth R. T.; Beverley, Katie; Clifton, Nick; Walpole, Gary (Emerald, 2026)
Purpose: With the orientation for sustainability, circular economy (CE) is promoted through “exaptive events” such as educational workshops. Social enterprises (SEs) play an important role in CE transformation but face significant challenges. Whilst exaptation theory is well-studied in commercial context, less is known about its role in driving SE innovation. Thus, this paper aims to answer the following research question: how can exaptive events facilitate circular economy innovation in the context of social enterprise? Design/methodology/approach: This paper conducted an in-depth case study of a CE-themed project in the UK, engaging with the event organisers and SE participants. Data were collected through interview, observation and secondary documentation. Using a structured inductive approach, this paper identified key themes and generated a grounded theoretical model. Findings: Four themes are identified as: 1) knowledge sharing, 2) exaptive pools, 3) exaptive relations and 4) challenges to SE sustainability and success. Findings indicate that exaptive events can enhance SE innovation. Also, the connection of exaptive events, tools and relations helps overcome barriers in finance, commercial viability, social value and cross-sector collaboration. Nevertheless, finance and commercial viability inhibit SE’s further effective innovations. Originality/value: By offering a new perspective – exaptive events – on SE innovation, this study extends the application of exaptive innovation beyond private-sector product commercialisation to tackling challenges faced by SEs. This study indicates that practitioners and policymakers can leverage exaptive events to promote sustainable development. For SEs, collaboration with public sectors through these events promotes resource sharing, joint innovation and commercialisation opportunities.
Keywords: Social enterprise; Social innovation; Exaptive innovation; Circular economy; Local economy; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; 12 Responsible Consumption and Production; 35 Commerce, management, tourism and services